Regulation of The Use of Gadgets During the Covid-19 Pandemic is Needed to Prevent Emotional Problems in Children - Lintang Firdhani Nabila Puteri; Ariani Ariani; Hera Dwi Novita (Jurnal Ilmu Kedokteran Keluarga, 2022)
Background: The number of children's use of gadgets during the COVID-19 pandemic has increased due to the quarantine policy by the government so it has an impact on children's emotional problems. Objective: To determine the relationship between the use of gadgets during the COVID-19 pandemic on children's emotional problems based on the duration of use and ownership of gadgets. Methods: This study used an observational analytic design with a cross-sectional method. The research instrument used an online questionnaire. The sampling method used is simple random sampling. The independent variable is the duration of gadget use and gadget ownership, while the dependent variable is the child's emotional problem. The duration of gadget use is categorized into less than 2 hours and more than 2 hours per day. Ownership of gadgets is categorized as self-owned or not. Emotional problems were categorized by severity (none, mild, severe). Data analysis with Mann-Whitney test using SPSS 25. Results: The number of respondents was 116 children, 13 men (9,56%), and 123 women (91,44%), aged 6-12 years 13 people (9,56%) and 13-18 years old 123 people (91,44%), have their own gadget 2 people (1,5%) and do not have a gadget 134 people (98,5%), the duration of using gadgets is less than 2 hours per day 28 people (20,6%) and more than 2 hours per day 108 people (79,4%). Based on the Mann-Whitney test, there is a relationship between the duration of using gadgets and the level of children's emotional problems (p = 0,017), while gadget ownership is not associated with children's emotional problems (p = 0,431). Conclusion: Regulation is needed to limit the duration of gadget use during the COVID-19 pandemic to prevent children's emotional problems. Abstrak Latar Belakang: Jumlah penggunaan gadget anak-anak di masa pandemi COVID-19 mengalami peningkatan akibat kebijakan karantina oleh pemerintah sehingga berdampak pada masalah emosional anak. Tujuan: Untuk mengetahui hubungan penggunaan gadget di masa pandemi COVID-19 terhadap masalah emosional anak berdasarkan durasi penggunaan dan kepemilikan gadget. Metode: Penelitian ini menggunakan desain analitik observasional metode cross sectional. Instrumen penelitian menggunakan kuesioner online. Metode pengambilan sampel menggunakan simple random sampling. Variabel bebas adalah durasi penggunaan gadget dan kepemilikan gadget, sedangkan variabel terikat adalah masalah emosional anak. Durasi penggunaan gadget dikategorikan menjadi kurang dari 2 jam dan lebih dari 2 jam per hari. Kepemilikan gadget dikategorikan sebagai kepemilikan sendiri dan tidak. Masalah emosional dikategorikan berdasarkan tingkat keparahan (tidak ada, ringan, berat). Analisis data dengan uji Mann Whitney mengunakan SPSS 25. Hasil: Jumlah responden 116 anak, laki-laki 13 orang (9,56%), dan perempuan 123 orang (91,44%), berusia 6-12 tahun 13 orang (9,56%) dan 13-18 tahun 123 orang (91,44%), memiliki gadget sendiri 2 orang (1,5%) dan tidak memiliki gadget 134 orang (98,5%), durasi penggunaan gadget kurang dari 2 jam per hari 28 orang (20,6%) dan lebih dari 2 jam per hari 108 orang (79,4%). Berdasarkan uji Mann Whitney terdapat hubungan antara durasi penggunaan gadget dengan tingkat masalah emosional anak (p=0,017), sedangkan kepemilikan gadget tidak terkait dengan masalah emosional anak (p=0,431). Kesimpulan: diperlukan regulasi untuk membatasi durasi penggunaan gadget saat pandemi COVID 19 untuk mencegah masalah emosional anak. Kata Kunci: durasi, kepemilikan gadget, emosi, anak. Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332705